HUBUNGAN KETAATAN DIET DAN OLAHRAGA DENGAN KADAR GULA DARAH DI POLIKLINIK PENYAKIT DALAM RSUD KAB. SIAK - Anita Syarifah, Hardiyanti Bachron (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Diabetes mellitus is a chronic disorder of metabolic disorder characterized by an increase in blood clucose (hyperglycemia). Diet obedience is the behavior of humans or a group of humans in meeting the need for food that includes attitude, beliefs and eating choices. And lack of exercise is a factor one of the factors that play a role that causes insulin resistance in type 2 diabetes mellitus. The purpose of this study to analyze the relationship of ketetatan diaet and exercise with blood sugar kada in people with diabetes mellitus type 2 in polyclinic disease in RSUD Kab. Siak. The research method used is correlation design with cross sectional study approach. The sampling technique in this research is using accidental sampling technique. The sample in this study amounted to 32 respondents. The data were collected by using questionnaires. Data processing using SPSS program with Pearson correlation test with significance level 95% (α = 0,05). The statistic test used is chi-square test to know the relationship of dietary and exercise obedience with sugar content of DM patient. The result of the research was found that there was a correlation between dietary obedience with blood sugar level of DM patient (p = 0,004 <α) and there was a sport relation with blood sugar level of DM patient p = 0,010 <α).Keywords: Obedience diet, exercise, blood sugar level, diabetes mellitus type 2. References: 15 books 2005-2016 and 13 journals 2011-2018